Frequency and Illumination Effects on ALIKIICdTe Junction - Al-Ani, S.; El-Saminani, A.; Al- Samaraece, A. (Iraqi Journal of Science, 2025)
Thin films of K! have been grown under vacuum on the CdTe semiconductor This paper mainly deals with frequency and filamination effects on C-V and G-V characteristics of the metad polycrystaline Kl n-type Cdle structure. For sweep rates greater than 6 Vs the C-V curves do not show any significant hysteresis The measured capacitance was inercased under illumination and it was interpreted in tena of reducing in depletion layer white due to the internal photo voltage. The flat barid capteitence Ceas changed abruptly when C took place at low frequency, but as niga frequency the Cr was decreased slowly